Beyond cash - Kalisa, Fugece; Manyenye, Deus (Technical Centre for Agricultural and Rural Cooperation, 2014)
In just three years' time, SmartMoney has grown from a small intervention targeting market inefficiencies between rural farmers and agriculture organisations to a community-wide rural payment and savings solution with more than 20,000 subscribers